POLITICAL LEGAL IN SETTING THE AGE LIMIT FOR MARRIAGE IN LAW NUMBER 16 OF 2019 AND MARRIAGE DISPENSATION IN PERMA NUMBER 5 OF 2019 - Ismaidar; Alimal Yusro Siregar (RADJA PUBLIKA, 2024)
Law Number 16 of 2019 Amendments to Law Number 1 of 1974 concerning Marriage increases the minimum age for marriage for both men and women to 19 years. This is not just equalizing the minimum age for men and women, but there are government legal policies to improve the quality of Indonesian marriages. The age limit for marriage for citizens is in principle intended to ensure that couples who are getting married are expected to have maturity of thought, mental maturity and adequate physical strength. The legal politics of marriage dispensation in Indonesia are related to Marriage Law. Marriage dispensation is regulated in the law because the minimum age limit for marriage has been changed to 19 years for both sexes. Marriage dispensation legal policies are influenced by philosophical and sociological considerations such as justice, benefit, expediency and legal certainty. PERMA Number 5 of 2019 provides guidelines and standards for judges in considering and determining dispensational marriages and paying attention to the best interests of children. However, clearer clarification is needed from the State regarding the emergency situation that allows marriage dispensations and stricter procedures for marriage dispensation to prevent premature marriage.